Current Opinion on Endovascular Therapy for Emergent Large Vessel Occlusion Due to Underlying Intracranial Atherosclerotic Stenosis - Kang, Dong-Hun; Yoon, Woong (Korean journal of radiology, 2019)
For recanalization of emergent large vessel occlusions (ELVOs), endovascular therapy (EVT) using newer devices, such as a stent retriever and large-bore catheter, has shown better patient outcomes compared with intravenous recombinant tissue plasminogen activator only. Intracranial atherosclerotic stenosis (ICAS) is a major cause of acute ischemic stroke, the incidence of which is rising worldwide. Thus, it is not rare to encounter underlying ICAS during EVT procedures, particularly in Asian countries. ELVO due to underlying ICAS is often related to EVT procedure failure or complications, which can lead to poor functional recovery. However, information regarding EVT for this type of stroke is lacking because large clinical trials have been largely based on Western populations. In this review, we discuss the unique pathologic basis of ELVO with underlying ICAS, which may complicate EVT procedures. Moreover, we review EVT data for patients with ELVO due to underlying ICAS and suggest an optimal endovascular recanalization strategy based on the existing literature. Finally, we present future perspectives on this subject.